Transitional Justice in Rwanda: Analysis of Reconciliation Initiatives in Musha Village - Jakubėnaitė, Urtė (Politologija, 2021)
The article examines how reconciliation is perceived at the individual level. This particular case study analyses what types of reconciliation practices exist in Musha village and whether or not the inhabitants see it as effective ones. In an attempt to investigate the reconciliation definition from the local people’s perspective and to observe their community-level experiences, ethnographic fieldwork in Rwanda has been conducted. This study reveals that locals understand reconciliation in the same way as the government authorities proclaim. Data gathered during this field trip indicate the significance of reconciliation as controlled by the national government. As a consequence, the people are not able, and at the same time, are not really concerned about rethinking reconciliation in other possible ways. Furthermore, this concludes the fact that the central authorities have become able to peacefully construct the narrative of forced reconciliation, while social exclusion in the country still robustly prevails.
Keywords: transitional justice; reconciliation; grassroots initiatives; community; Rwanda; Musha village; fieldwork